Analysis Of Emotional Maturity That Impacts Career Decision-Making Among Adolescents - Aah Khoriah; Ayu Lestari (Al-Makki Publisher, 2023)
Emotional maturity is the most important thing for adolescents in the process of solving problems by determining choices from various options or alternatives to determine an action in achieving the desired goals in the form of career decision making. The purpose of this paper is to analyze the emotional maturity that impacts career decision-making among adolescents. The research method used is qualitative descriptive method. With qualitative types and categorized into two types, namely primary data and secondary data. The results showed that high emotional maturity was positively associated with better career decision making. Teens who have more mature emotional maturity tend to have a better understanding of their interests, talents, and personal values, and have a better ability to cope with the pressures and uncertainties of choosing a career. In addition, other factors such as parental influence, interests and talents, societal views, and knowledge of career choices also influence a teenager's career decision making. Positive parental influence, support from the social environment, and access to information about various career options have an important role to play in helping adolescents make good career decisions. This research contributes to understanding the importance of emotional maturity in adolescent career decision-making. The implications of this research could be used by education professionals and career counselors to assist adolescents in developing emotional maturity and making better career decisions